Consulting Project Marketing Plan for Armaos Courier/Armaos Group. - Epaminondas Koronis; Vousvoukis Paraskevas (2009)
Proceeding, Emails, Material Used for the Project, Information about Armaos Group, Information about the Sector, Material from Internet.